Self-reported Emergency Skills Competence among Pre-hospital Emergency Personnel in a Rural Area of Indonesia - Benny Arief Sulistyanto; Irnawati Irnawati; Retno Sugesti; Devi Listiana; Sri Hayati; Evra Yusandra (Proceedings Series on Health & Medical Sciences, 2022)
Background: Pre-hospital emergency medical services (EMS) personnel are responsible for providing intervention outside of the hospital setting. Consequently, the pre-hospital emergency personnel demand high capability of the personnel to perform emergency aid at the scene and during transport to the hospital. Objective: The purpose of this study is to explore emergency skills competence among pre-hospital emergency personnel in the area on the north coast of Java. Method: This study used the Essential Knowledge and Skills Questionnaire (EKSQ) as the instrument. There was 42 pre-hospital emergency personnel participated in this study. Results: This study revealed that most pre-hospital emergency personnel are nurses (93%). Most respondents reported not having sufficient competency in resuscitation (2,78 of 5 points) and giving medication (2,81 of 5 points). Age and experience were significantly correlated with pre-hospital emergency personnel's competence. Conclusion: This study concluded that there was a lack of competence in resuscitation. Hence, continuous professional-development courses are necessary to maintain pre-hospital emergency personnel's professional proficiency.